Endovascular treatment of cephalic arch stenosis in brachiocephalic arteriovenous fistulas: A systematic review and meta-analysis. Issue 4 (July 2019) - D'cruz, Reuban Toby; Leong, Sze Wai; Syn, Nicholas; Tiwari, Alok; Sannasi, Vikram Vijayan; Singh Sidhu, Harvinder Raj; Tang, Tjun Yip
Purpose: The aim of this study is to appraise the current literature on the endovascular management options and their outcomes of cephalic arch stenosis in the setting of a failing brachiocephalic fistula for hemodialysis. Methods: A systematic search of the literature was performed using PubMed, Embase, and Google Scholar from January 2000 to December 2017 in accordance with the PRISMA guidelines to investigate the outcomes of endovascular management of cephalic arch stenosis. Data from randomized controlled trials and observational studies, published in the English language, were extracted to determine pooled proportion of primary and secondary patency, using a random-effects meta-analysis. Subgroup analyses of stent grafts, bare metal stents, and percutaneous transluminal angioplasty outcomes were performed. Results: Of the 125 total studies, 11 were included for analysis by consensus. Overall, 457 patients were reviewed and analyzed for primary and secondary patency rates at 6 and 12 months post-treatment. There was significantly higher primary patency at both 6 and 12 months in the stent graft group compared to those who received bare metal stents or percutaneous transluminal angioplasty (relative risk = 0.30–0.31, relative risk = 0.34–0.59, respectively; p < 0.01). Higher secondary patency rates were noted in the bare metal stents cohort compared to the percutaneous transluminal angioplasty cohort at 12 months (relative risk = 0.17, 95% confidence interval = 0.07–0.26; p < 0.01). Conclusion: This study demonstrated a significant benefit in using stent grafts in cephalic arch stenosis compared to bare metal stents or percutaneous transluminal angioplasty with higher primary and secondary patency rates.